Developing Android-Based English Vocabulary Learning Materials for Primary School Students - Made Hery Santosa; I Putu Surya Pratama; I Nyoman Adi Jaya Putra (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
This study intended to develop an android-based application for English vocabulary learning for primary school students. By implementing Design and Development design model, the researcher underwent three main stages namely; 1) Design, 2) Development, and 3) Evaluation. Through the use of questionnaires and interview guide, the needs were assessed. The results showed that the primary school students need more time to learn English and emphasize more on vocabulary learning. The primary school students need a smartphone application which provides vocabulary practice, test and entertainment about the topics learnt in the class. The smartphone application was developed in Android Package Kit (APK) format designed by using Microsoft Power Point. Contrasted to others, this smartphone application provides vocabulary practices, quizzes, and games for all topics that 4, 5, and 6 graders need to learn. The smartphone application was tested and evaluated by 5 English teachers and 2 technology experts to find out the quality. The results showed that the application has a very good quality and ready to be installed and used in Android smartphone. An effective use of the application with meaningful learning activities for vocabulary learning for young learners are strongly suggested.